إجراءات ومتطلبات إعادة هيكلة وتأهيل تنافسية شعبة الزيتون ومشتقاتها في الجزائر - بن رجم محمد خميسي; حدادة فريد (My University, 2019)
تهدف هذه الدراسة إلى تسليط الضوء على أهم المتطلبات والإجراءات التنظيمية والتسييرية التي يمكن من خلالها تحسين والرفع من تنافسية شعبة الزيتون ومشتقاتها في الجزائر، حيث تعد هذه الشعبة من بين القطاعات الاستراتيجية التي تعمل الجزائر على تطويرها، وذلك بإعادة هيكلتها وتأهيلها للوصول بمنتجاتها لتنافسية عالية على الصعيدين الوطني والدولي. وقد تم الإستعانة بالمنهج الاستقرائي للإجابة على إشكالية الدراسة. حيث توصلت نتائج الدراسة إلى ضعف عمليات المكننة في عمليات الجني، ناهيك عن نقص العقار الصناعي والزراعي وهو ما يؤثر سلبا على تطوير البنية التحتيية لمؤسسات التحويل والتعبئة لشعبة الزيتون ومشتقاته، كما أوصت الدراسة بضرورة توسيع المساحات المزروعة بأشجار الزيتون ومرافقة المؤسسات المنتجة والمحولة لهذه الشعبة. This study aims to shed light on the most important requirements and regulatory and administrative procedures that can improve and increase the competitiveness of the olive and derivatives branch in Algeria. This branch is one of the strategic sectors that Algeria is working on developing, by restructuring and rehabilitating for access to competitive products at the national and international levels. We used the inductive method to answer the problem of study, so the study concluded that lack of mechanization processes in harvesting operations, in addition to the lack of industrial and agricultural property, which negatively affects the development of the infrastructure of the conversion and packaging institutions of olive branch; the study also recommended the need to expand olive groves and accompanying producing and converting olive enterprises of this branch.